PSYCHOLOGICAL FACTORS IN DETERMINING THE MANIFESTATION OF ABILITIES IN STUDENTS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
In psychology, one of the most important types of individual psychological characteristics is ability. Students' abilities appear and develop in different ways as a result of their interests and work on themselves. Depending on the nature of the activity, the ability is manifested in different ways depending on the chosen profession, and some individuals are capable in several areas.